Coordinated transfer of DNA between Pol θ and Pol δ resets microhomology choice during double-strand break repair - Yuzhen Li; Mark Returan; Adele T. Guerin; April M. Averill; Dorcas Oladapo; Sylvie Doublié; Richard D. Wood (Proceedings of the National Academy of Sciences, 2025)
DNA polymerase theta (Pol θ)-mediated end joining (TMEJ) initiates DNA double-strand break repair by using short homologies (microhomologies) between single-stranded DNA tails. This repair process is particularly important in cancer cells defective in homologous recombination. The exonuclease function of DNA polymerase delta (Pol δ) has been identified as an essential component for TMEJ, functioning to remove unpaired bases flanking a microhomology (MH). It is not known if the exonuclease removes all unpaired bases at once and how this removal might affect subsequent MH selection. Here, we reconstituted a functional TMEJ repair process using purified human Pol θ and Pol δ. We find that when Pol δ exonuclease excises a nucleotide to generate a new 3′ terminus, Pol θ initiates a new MH search. Pol δ exonuclease removes a single nucleotide at a time, rather than cleaving an unpaired flap, and then transfers the DNA tail to the polymerase site of Pol θ. Specific primer-grasp amino acids in the polymerase domain of Pol θ are important for internal MH anchoring. The helicase-like domain of Pol θ harbors two activities which are recapitulated in reconstituted reactions: strand-capture to bring single-strand tails together and an ATPase activity that alleviates suppression of TMEJ by ssDNA binding protein RPA. This functional reconstitution of TMEJ advances the understanding of how two polymerases with three enzymatic activities orchestrate double-strand break repair.